Is Mobility of Technical Personnel a Source of R&D Spillovers? - Møen, Jarle (Journal of Labor Economics, 2005)
Labor mobility is considered to be an important source of knowledge externalities, making it difficult for firms to appropriate returns to research and development (R&D). Interfirm transfers of knowledge embodied in people should be analyzed within a human capital framework. Testing such a framework, I find that the technical staff in R&D‐intensive firms pays for the knowledge they accumulate on the job through lower wages early in their career. They later earn a return on these implicit investments through higher wages. This suggests that the potential externalities associated with labor mobility are, at least partially, internalized in the labor market.